Calcium requirement for gliding motility in myxobacteria. - Womack, B J (1989)
The ability to glide on a solid surface was inducible by calcium ion in Stigmatella aurantiaca. The induction of motility but not motility itself was prevented by chloramphenicol and erythromycin. Calcium ion was also required for cells to glide, even when they were previously induced. The ability of Myxococcus xanthus to glide in groups using the S motility system but not as single cells (A system) was prevented by chloramphenicol and erythromycin.